Periodic Methylation Patterns in the Background Mucosa of Gastric Cancer - Sang-Woong Kim; Jung-Hwan Oh; Tae Ho Kim; Joon-Sung Kim; Seung-Jin Hong (The Korean Journal of Helicobacter and Upper Gastrointestinal Research, 2019)
Background/Aims Gastrointestinal glandular stem cells renew every 8 years. New stem cells with impeded housekeeping gene methylation have unstable phenotypes and are prone to transform into malignant cells. Age-related changes in methylation in the gastric mucosa were evaluated to define the period of cancer-prone stem cell replacement.Materials and Methods Endoscopic biopsy specimens of normal-appearing gastric mucosa were obtained from 148 Helicobacter pylori-negative controls, 124 H. pylori-positive controls, and 69 gastric cancer patients with closed-type mucosal atrophy. Methylation-variable sites of two stomach-specific genes (TFF2 and TFF3) and four housekeeping genes (CDH1, ARRDC4, MMP2, and CDKN2A) were analyzed using radioisotope-labeled methylation-specific polymerase chain reaction. Age-related methylation was evaluated depending on the gastric mucosal atrophy at 2-year intervals. Results TFF2 methylation peaked periodically at 40 to 41, 48 to 49, 56 to 57, and 64 to 65 years of age in H. pylori-negative controls. Periodic peaks of TFF2 methylation were also found in H. pylori-positive controls. Housekeeping-gene methylation troughed at 48 to 49, 56 to 57, and 68 to 69 years of age in cancer patients. Trough methylation of CDH1 and ARRDC4 was lower in cancer patients than in H. pylori-positive controls. Conclusions Methylation peaks of stomach-specific TFF2 in controls and methylation troughs of housekeeping genes in cancer patients were found every 8 years. Periodic methylation patterns may be used to identify individuals at high risk for gastric cancer.